If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5m + 27 + -3(m + -1) = 8m + -1(6m + -3) + -7m + 9 Reorder the terms: -5m + 27 + -3(-1 + m) = 8m + -1(6m + -3) + -7m + 9 -5m + 27 + (-1 * -3 + m * -3) = 8m + -1(6m + -3) + -7m + 9 -5m + 27 + (3 + -3m) = 8m + -1(6m + -3) + -7m + 9 Reorder the terms: 27 + 3 + -5m + -3m = 8m + -1(6m + -3) + -7m + 9 Combine like terms: 27 + 3 = 30 30 + -5m + -3m = 8m + -1(6m + -3) + -7m + 9 Combine like terms: -5m + -3m = -8m 30 + -8m = 8m + -1(6m + -3) + -7m + 9 Reorder the terms: 30 + -8m = 8m + -1(-3 + 6m) + -7m + 9 30 + -8m = 8m + (-3 * -1 + 6m * -1) + -7m + 9 30 + -8m = 8m + (3 + -6m) + -7m + 9 Reorder the terms: 30 + -8m = 3 + 9 + 8m + -6m + -7m Combine like terms: 3 + 9 = 12 30 + -8m = 12 + 8m + -6m + -7m Combine like terms: 8m + -6m = 2m 30 + -8m = 12 + 2m + -7m Combine like terms: 2m + -7m = -5m 30 + -8m = 12 + -5m Solving 30 + -8m = 12 + -5m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '5m' to each side of the equation. 30 + -8m + 5m = 12 + -5m + 5m Combine like terms: -8m + 5m = -3m 30 + -3m = 12 + -5m + 5m Combine like terms: -5m + 5m = 0 30 + -3m = 12 + 0 30 + -3m = 12 Add '-30' to each side of the equation. 30 + -30 + -3m = 12 + -30 Combine like terms: 30 + -30 = 0 0 + -3m = 12 + -30 -3m = 12 + -30 Combine like terms: 12 + -30 = -18 -3m = -18 Divide each side by '-3'. m = 6 Simplifying m = 6
| N/6=9/10 | | 440/(2 | | (D^2-4D+4)y=x^3 | | 600x-0.03=100x+0.57 | | 40+5p=2p | | 10y=3-4x | | 0.025(a+4)=1.2415 | | 0.025(a+4)= | | 59.50-0.25x=30.00 | | 8p=3p+17 | | 6x+10y+15z=1 | | g(x)=3x/x6 | | 17240=-48n+23000 | | g(x)=7x/x | | 5m=7m-2 | | 3x-75=15x+5 | | (px-y)(py+x)=2p | | 5m=7m+2 | | g(x)=x4/x2 | | 29+(3x+1)=90 | | 6b-10=8 | | 20+8a=-4 | | 3x-75=15+5 | | 5t=48 | | 3x+1+5x-6=36 | | -21=3y | | 0.07x=2.52 | | g(x)=sqrx-8 | | 5x^6-3x^3-110=0 | | 8+2=26106 | | F(5)=4x^2+2x^2-4 | | -9(6+u)-2u=-2 |